2017
DOI: 10.17511/jopm.2017.i04.08
|View full text |Cite
|
Sign up to set email alerts
|

Study of blood donor profile in a blood bank attached to a medical college hospital - a retrospective study

Abstract: Background: Blood Transfusion Services (BTS) are the vital part of modern health care system without which efficient medical care is impossible. To make blood donation safe and increase the confidence of the masses in voluntary blood donation, many safety measures are implemented by the blood transfusion community. The most important of all safety measures is donor selection. Stringent, meticulous and serious donor screening is necessary to afford protection to blood donors and recipients. Aim & Objectives: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…12 In our study majority of donors were voluntary. Majority of donors were replacement, 3,4 in other studies from India. Study by Christopher R France et al had shown donor anxiety decreases blood donor retention.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…12 In our study majority of donors were voluntary. Majority of donors were replacement, 3,4 in other studies from India. Study by Christopher R France et al had shown donor anxiety decreases blood donor retention.…”
Section: Discussionmentioning
confidence: 88%
“…In study by N Rajendra et al showed 83.7 percent were males. 3 More than 95 percentage of donors were males in study by Unnikrishnan et al in south coastal India. 2 Study from Kolkata by S Duttaetal showed females formed 9.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…John et al-4.92% [2], Krishna et al-1.55%[9], Sunder P et al-11.27% [10], Sareen R et al-8.39% [12], Chaudhary et al-8.68% [13], Girish et al-2.66% [14], Agarwal et al-8.39% [15], Rathod et al-5.98%[16]. This may be due to lack of awareness, fear, misconception about physiological reasons, or lack of motivation.…”
mentioning
confidence: 99%